Necessary conflict on the homefront: a content analysis of marriage and relationship education resources used by military couples - Witcher, Kathleen M. (Kansas State University, 2013)
As we pass the decade mark of the Global War on Terrorism, the hidden causalities, such as the long-term impact of multiple deployments on marriages, become more apparent. Military couples experiencing repeated combat-related deployments are at an increased risk for marital distress, especially relationships that exhibit negative interaction patterns. Marriage and relationship education programs have the potential to equip military couples with conflict management skills, such as positive reframing and open communication, to increase marital satisfaction. This content analysis examined three relevant marriage and relationship education resources – PREP for Strong Bonds, ScreamFree Marriage, and Marriage LINKS - presently utilized by military couples. Each marriage and relationship education program reviewed utilized similar themes found in the research literature. Results of the analysis indicate a combination of their skill sets, accompanied by a concentration on specific challenges unique to military marriages, would be more effective in improving marital satisfaction than the models as they currently stand.
Keywords: Conflict; Marriage; Military couples; Marriage education; Individual & Family Studies (0628)